Modeling the influence of electron beam energy distribution on quality of radiation processing - Lazurik, Valentine T.; Lazurik, Valentina M.; Popov, Gennadiy F.; Zimek, Zbigniew (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2018)
The obtained values of most probable energy and practical range have been compared to values calculated according to the formula proposed by the internationally recognized documents. The presented results of the study are focused on the issue of the influence of electron beam energy spread on the depth dose distribution and practical range of electron beam in the irradiated material. The computational experiments have been performed using the Monte-Carlo simulation method for modeling the electron beam energy spectra and depth dose distributions of electrons in aluminum target. Obtained values of most probable energy Ep and practical range Rp have been compared to the values calculated according to formula proposed by the internationally recognized report. The value of a practical range of electrons Rp strongly depends on electron beam energy spread, even in case when value of most probable energy Ep of electrons in the beam is unchanged. Results of computer experiments show that in case of a large energy spread, and presence of asymmetry of electron energy distribution, the electrons energy can’t be determined properly by empirical formulas included to the international standards.